Knockdown of Pyruvate Carboxylase or Fatty Acid Synthase Lowers Numerous Lipids and Glucose-Stimulated Insulin Release in Insulinoma Cells - MacDonald, Michael J. (2013)
We previously showed that knockdown of the anaplerotic enzyme pyruvate carboxylase in the INS-1 832/13 insulinoma cell line inhibited glucose-stimulated insulin release and glucose carbon incorporation into lipids. We now show that knockdown of fatty acid synthase (FAS) mRNA and protein also inhibits glucose-stimulated insulin release in this cell line. Levels of numerous phospholipids, cholesterol esters, diacylglycerol, triglycerides and individual fatty acids with C(14)-C(24) side chains were acutely lowered about 20% in glucose-stimulated pyruvate carboxylase knockdown cells over a time course that coincides with insulin secretion. In FAS knockdown cells glucose carbon incorporation into lipids and the levels of the subclasses of phospholipids and cholesterol ester species were lower by 20–30% without inhibition of glucose oxidation. These studies suggest that rapid lipid modification is essential for normal glucose-stimulated insulin secretion.